Effect of Internal Control Risk in Determining Audit Fees - Aziza, Shifa Miarti; Apandi, R. Nelly Nur; Kustiawan, Memen (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
The existence of low internal control is always associated with the amount of audit fees that will be paid by the company, while good internal control can reduce audit fees. Moreover, the audit fee is an important thing for an auditor in carrying out his duties. Therefore, this study aims to find out how internal control affects the determination of audit fees. The method used in this study is a quantitative method with a descriptive and associative approach. The data for this study uses secondary data available on the Stock Exchanges in Indonesia, Malaysia, and Thailand in 2022. The results in this study indicate that internal control cannot affect audit fees because the determination of existing audit fees is based on an agreement made by the auditor and the company with a look at the various factors that exist in the company.